Analysis of the Behavior of Glucose in Diabetic and Pregnant Rats at Two Weeks of Gestation - Pérez Pérez, Jorly Alberto; Sánchez DomÃnguez, Sandy; Fernández GarcÃa, Adolfo A.; Gómez, Tahiry; Bequer, Leticia (Revista Cubana de Informática Médica, 2025)
An application of a study to various data collected from an experimental model of diabetes in Wistar rats developed by the Unidad de Investigaciones Biomédicas of the Universidad de Ciencias Médicas de Villa Clara, which is based on the proposal of a mathematical model that is analyzed in previous works, is shown here. In this way, the real behavior of blood glucose is approximated to each instant of time for the course of 5 hours, once the ingestion of a dose for each rat has been carried out. The curves obtained from the model in the different cases can be compared between them. In addition, with graphic representations, several parameters of great importance for decision making are identified and the difference is represented when we are in the presence of diabetic and pregnant rats with their respective controls. Keywords: insulin and glucose interaction; pregnancy diabetes; gestational diabetes; behavior of insulin-glucose through differential equations; insulin-glucose dynamics; expected value for variation of glucose concentration. RESUMEN Se muestra una aplicación de un estudio a diversos datos recolectados de un modelo experimental de diabetes en ratas Wistar desarrollado por la Unidad de investigaciones biomédicas de la Universidad de Ciencias Médicas de Villa Clara, el cual se basa en la propuesta de un modelo matemático que se analiza en trabajos previos. De esta manera, se aproxima el comportamiento real de la glucosa en sangre en cada instante de tiempo durante el transcurso de 5 horas una vez realizada la ingesta de una dosis para cada rata. Las curvas obtenidas en los diferentes casos a partir del modelo se pueden comparar entre sí. Además, con las representaciones gráficas se identifican varios parámetros de gran importancia para la toma de decisiones y se representa la diferencia cuando estamos en presencia de ratas diabéticas y gestantes con sus respectivos controles. Palabras clave: interacción insulina-glucosa; diabetes gestacional; comportamiento insulina-glucosa a través de ecuaciones diferenciales; dinámica insulina-glucosa; valor esperado para la variación de la concentración de glucosa.